Write each expression in Exercises \( 1-14 \) in the form \( 2^{k x} \) or \( 3^{k x} \), for a suitable constant \( k \). \( \begin{array}{ll}\text { 1. } 4^{x},(\sqrt{3})^{x},\left(\frac{1}{9}\right)^{x} & \text { 2. } 27^{x},(\sqrt[3]{2})^{x},\left(\frac{1}{8}\right)^{x} \\ \begin{array}{ll}\text { (3) } 8^{2 x / 3}, 9^{3 x / 2}, 16^{-3 x / 4} & \text { 4. } 9^{-x / 2}, 8^{4 x / 3}, 27^{-2 x / 3} \\ \text { 5. }\left(\frac{1}{4}\right)^{2 x},\left(\frac{1}{8}\right)^{-3 x},\left(\frac{1}{81}\right)^{x / 2} & \text { 6. }\left(\frac{1}{9}\right)^{2 x},\left(\frac{1}{27}\right)^{x / 3},\left(\frac{1}{16}\right)^{-x / 2}\end{array}\end{array} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
Let's transform the expressions to the forms \( 2^{k x} \) or \( 3^{k x} \): 1. \( 4^{x} = (2^2)^{x} = 2^{2x} \) \( (\sqrt{3})^{x} = (3^{1/2})^{x} = 3^{x/2} \) \( \left(\frac{1}{9}\right)^{x} = (9^{-1})^{x} = (3^2)^{-x} = 3^{-2x} \) 2. \( 27^{x} = (3^3)^{x} = 3^{3x} \) \( (\sqrt[3]{2})^{x} = (2^{1/3})^{x} = 2^{x/3} \) \( \left(\frac{1}{8}\right)^{x} = (8^{-1})^{x} = (2^3)^{-x} = 2^{-3x} \) 3. \( 8^{2x/3} = (2^3)^{2x/3} = 2^{2x} \) \( 9^{3x/2} = (3^2)^{3x/2} = 3^{3x} \) \( 16^{-3x/4} = (2^4)^{-3x/4} = 2^{-3x} \) 4. \( 9^{-x/2} = (3^2)^{-x/2} = 3^{-x} \) \( 8^{4x/3} = (2^3)^{4x/3} = 2^{4x} \) \( 27^{-2x/3} = (3^3)^{-2x/3} = 3^{-2x} \) 5. \( \left(\frac{1}{4}\right)^{2x} = (4^{-1})^{2x} = (2^2)^{-2x} = 2^{-4x} \) \( \left(\frac{1}{8}\right)^{-3x} = (8^{-1})^{-3x} = (2^3)^{3x} = 2^{9x} \) \( \left(\frac{1}{81}\right)^{x/2} = (81^{-1})^{x/2} = (3^4)^{-x/2} = 3^{-2x} \) 6. \( \left(\frac{1}{9}\right)^{2x} = (9^{-1})^{2x} = (3^2)^{-2x} = 3^{-4x} \) \( \left(\frac{1}{27}\right)^{x/3} = (27^{-1})^{x/3} = (3^3)^{-x/3} = 3^{-x} \) \( \left(\frac{1}{16}\right)^{-x/2} = (16^{-1})^{-x/2} = (2^4)^{x/2} = 2^{2x} \)